Differences in Blood Pressure Using Mercury and Digital Sphygmomanometer in Stand and Supine Positions - Lusiana, Nova; Kusumawati, Estri (International Conference on Sustainable Health Promotion, 2018)
One billion people in the world suffered hypertension in 2011 (WHO), and the prevalence will continue to increase. It predicted in 2025, as many as 29% of adults are getting a high blood pressure. Efforts made in controlling hypertension include increasing prevention and controlling community-based hypertension with "self-awareness" through regular blood measurements. Blood pressure can be checked using both manually and electric sphygmomanometer blood pressure. This study aims to know the differences in blood pressure measurement results between sistol and diastole, in a standing and supine position using manual and digital sphygmomanometer. This research is a laboratory observational study with the cross-sectional approach. The study population was students of the Biology Department, State Islamic University of Sunan Ampel Surabaya. The study was conducted at the integration laboratory in March 2018. The study found that the measurement of systolic and diastolic blood pressure in a standing position was higher than in supine position, there was a difference of 5-6 mmHg. Furthermore, blood pressure measurement using manual sphygmomanometer is higher than using digital sphygmomanometer, there is a difference of 5-8 mmHg in the measurement of systolic blood pressure, and 6-10 mmHg for diastolic blood pressure.